2019
DOI: 10.1093/carcin/bgz122
|View full text |Cite
|
Sign up to set email alerts
|

Organoid-based ex vivo reconstitution of Kras-driven pancreatic ductal carcinogenesis

Abstract: The organoid culture technique has been recently applied to modeling carcinogenesis in several organs. To further explore its potential and gain novel insights into tumorigenesis, we here investigated whether pancreatic ductal adenocarcinoma (PDA) could be generated as subcutaneous tumors in immunocompromised nude mice, by genetic engineering of normal organoids. As expected, acute induction of KrasG12Din vitro occasionally led to development of tiny nodules compatible with early lesions known as pancreatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…To date, it has been applied to various research fields, including infectious disease models, developmental biology, and epithelial regeneration . We also reported the establishment of murine organoid‐based carcinogenesis models for intestine, lung, hepatobiliary tract, and pancreas . These organoid culture techniques have now become common for patient‐derived samples from diverse types of cancer, which revealed that tumor‐derived organoids basically retained the morphology and genetic aberrations of the original tumors .…”
Section: Introductionmentioning
confidence: 99%
“…To date, it has been applied to various research fields, including infectious disease models, developmental biology, and epithelial regeneration . We also reported the establishment of murine organoid‐based carcinogenesis models for intestine, lung, hepatobiliary tract, and pancreas . These organoid culture techniques have now become common for patient‐derived samples from diverse types of cancer, which revealed that tumor‐derived organoids basically retained the morphology and genetic aberrations of the original tumors .…”
Section: Introductionmentioning
confidence: 99%
“…As the technology has advanced, organoids have been extensively used as a powerful tool of tumor research, particularly regarding the digestive system (Fig. 1) (7)(8)(9)(10)(11).…”
Section: Development and Merit Of Organoidsmentioning
confidence: 99%
“…The organoid model is more representative of typical physiological conditions compared with other models (4). Currently, the organoids for normal tissues, including the stomach (7), small intestine (8), liver (9), pancreas (10) and prostate (11), have been established successfully. Compared with PDCs, the patient-derived organoids (PDOs) not only reflect histopathological characteristics and the genomic and transcriptomic profiles of the original tumor, but also recapitulate the components of the tumor microenvironment (12).…”
Section: Introductionmentioning
confidence: 99%
“…Such tissue samples were collected in a hospital immediately after surgery, and processed the next morning following overnight transfer to the lab while maintained in a cold media ( Figure 1A). As a culture media, we tested the standard culture media supplemented with EGF, R-spondin-1, Noggin, Jagged-1, and Rho-associated, coiled-coil containing protein kinase (ROCK) inhibitor Y27632, which we have confirmed robustly applicable to organoid culture of murine primary cells from various organs and human gynecological neoplasms [20,22,23,30,32], to facilitate future cross-referencing of organoids from various organs.…”
Section: Propagation Of Patient-derived Organoids From the Cervical Smentioning
confidence: 99%
“…It has been applied to various research fields, including infectious diseases [17], developmental biology [18], and tissue regeneration [19]. By taking advantage of propagating normal stem cells in vitro, we have established murine organoid-based ex vivo carcinogenesis models for the intestine [20], lungs [21], hepatobiliary tract [22], and pancreas [23], by in vitro lentiviral gene transduction [24] or chemical treatment [25], followed by inoculation in the dorsal skin of nude mice. More recently, organoid culture techniques have been further applied to patient-derived tumor samples of diverse organs, which revealed that organoids basically retained the histological features and genetic aberrations of the original tumors [26][27][28].…”
mentioning
confidence: 99%